Incorporating culturally relevant pedagogy for international students in UK higher education: challenges and perspectives - Jennifer Park (Journal of Learning Development in Higher Education)
The number of international students in the United Kingdom’s (UK) higher education (HE) sector has significantly increased, yet research on pedagogical frameworks for these students remains limited, particularly within the context of private business schools. This study aims to address this gap by exploring the application of culturally relevant pedagogy (CRP) for international students in a UK HE private business school. CRP is a pedagogical framework that supports students’ intellectual, social, emotional, and political development by integrating their cultural backgrounds into teaching practices (Ladson-Billings, 2009), emphasising the importance of aligning teaching content and students’ cultural backgrounds (Yu, 2022). Using qualitative methodology, semi-structured interviews were conducted and analysed through thematic analysis with a deductive coding approach based on the three tenets of CRP: academic success, cultural competence, and critical consciousness. Findings suggested that participants, who were lecturers, were drawn to tenet 2, cultural competence, but also indicated challenges to incorporate CRP principles for international students within the UK HE private business school context. Contrary to the original CRP framework, findings in this study suggested that students and institutions, along with lecturers, should share the responsibility for students’ academic success. Unlike CRP in the United States (US) context, participants hesitated to discuss social issues with international students in the classroom. Given the challenges identified in this study, further study is necessary to reconceptualise CRP for international students, not only within UK HE private business schools but across the broader UK HE landscape.